Comprehensive Genome Scale Phylogenetic Study Provides New Insights on the Global Expansion of Chikungunya Virus (2016)
ABSTRACT: Since the India and Indian Ocean outbreaks of 2005 and 2006, the global distribution of chikungunya virus (CHIKV) and the locations of epidemics have dramatically shifted. First, the Indian Ocean lineage (IOL) caused sustained epidemics in India and has radiated to many other countries. Second, the Asian lineage has caused frequent outbreaks in the Pacific islands and in 2013 was introduced into the Caribbean, followed by rapid spread to nearly all of the neotropics. Further, CHIKV epidemics, as well as exported cases, have been reported in central Africa after a long period of perceived silence. To understand these changes and to anticipate the future of the virus, the exact distribution, genetic diversity, transmission routes, and future epidemic potential of CHIKV require further assessment. To do so, we conducted the most comprehensive phylogenetic analysis to date, examined CHIKV evolution and transmission, and explored distinct genetic factors associated with the emergence of the East/Central/ South African (ECSA) lineage, the IOL, and the Asian lineage. Our results reveal contrasting evolutionary patterns among the lineages, with growing genetic diversities observed in each, and suggest that CHIKV will continue to be a major public health threat with the potential for further emergence and spread.